2020
DOI: 10.1021/acsami.0c07169
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Jet Treatment of Polymers Enables Reagent-Free Covalent Attachment of Biomolecules for Bioprinting

Abstract: Three-dimensional (3D) bioprinting, where cells, hydrogels, and structural polymers can be printed layer by layer into complex designs, holds great promise for advances in medicine and the biomedical sciences. In principle, this technique enables the creation of highly patient-specific disease models and biomedical implants. However, an ability to tailor surface biocompatibility and interfacial bonding between printed components, such as polymers and hydrogels, is currently lacking. Here we demonstrate that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…The high temperature during plasma treatment, high RONS flux, and energetic UV emissions can lead to cell and tissue damage and must be controlled . Moreover, recent advances in biomedical sciences employ APPJs to locally functionalize and activate scaffolds for enhanced cell adhesion and controlled tissue growth or 3D bio-print biomolecules and cells . Following the development of APPJ-based biomedical technologies, safe and controlled plasma treatment is required when operating with biomaterials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high temperature during plasma treatment, high RONS flux, and energetic UV emissions can lead to cell and tissue damage and must be controlled . Moreover, recent advances in biomedical sciences employ APPJs to locally functionalize and activate scaffolds for enhanced cell adhesion and controlled tissue growth or 3D bio-print biomolecules and cells . Following the development of APPJ-based biomedical technologies, safe and controlled plasma treatment is required when operating with biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…32 Moreover, recent advances in biomedical sciences employ APPJs to locally functionalize and activate scaffolds for enhanced cell adhesion and controlled tissue growth 33 or 3D bio-print biomolecules and cells. 34 Following the development of APPJ-based biomedical technologies, safe and controlled plasma treatment is required when operating with biomaterials. Therefore, this study details a systematic investigation of the biological role of UV radiation from plasma, its contribution to the plasma−target interface, and interface control.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric Pressure Plasma Jet (APPJ) Functionalization of MEW Meshes: APPJ treatment settings were used as described previously, [24] with the following modifications: The APPJ was mounted in a 3D printer (FlSun i3 Prusa) modified in-house (Figure S1, Supporting Information). Marlin firmware was edited and uploaded with Arduino.…”
Section: Methodsmentioning
confidence: 99%
“…When gas flowing through capillaries is ionized by electric fields these devices are referred to as APP jets (APPJs). [21][22][23] Results have shown that dielectric barrier discharge APP systems [20] and APPJs [24] can be used to activate 2D polymeric surfaces to facilitate on-contact covalent immobilization of extracellular matrix proteins in a single-step, reagent-free process. Furthermore, the potential of APPJs to functionalize 3D polymeric meshes and subsequently covalently immobilize biomolecules without the need for wet chemistry processes has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Several gases are used for APPJ treatment of PE, for example, Argon [ 23 , 24 ] or compressed dried air (CDA) [ 19 ]. APPJ improves adhesion to PE in 3D bio-printed structures [ 25 ] or modifies the surface properties of shoulder implants made of ultra-high molecular weight polyethylene (UHMWPE) [ 26 ]. Compared with traditional polymer surfaces activation methods, such as flaming [ 27 , 28 ] or corona treatment [ 29 , 30 , 31 , 32 , 33 ], the APPJs allow the achievement of locally much higher values of surface free energy.…”
Section: Introductionmentioning
confidence: 99%